Taking Control: Campylobacter jejuni Binding to Fibronectin Sets the Stage for Cellular Adherence and Invasion - Konkel, Michael E.; Talukdar, Prabhat K.; Negretti, Nicholas M.; Klappenbach, Courtney M. (Frontiers in Microbiology, 2020)
Campylobacter jejuni, a foodborne pathogen, is one of the most common bacterial causes of gastroenteritis in the world. Undercooked poultry, raw (unpasteurized) dairy products, untreated water, and contaminated produce are the most common sources associated with infection. C. jejuni establishes a niche in the gut by adhering to and invading epithelial cells, which results in diarrhea with blood and mucus in the stool. The process of colonization is mediated, in part, by surface-exposed molecules (adhesins) that bind directly to host cell ligands or the extracellular matrix surrounding cells. In this review, we introduce the known and putative adhesins of the foodborne pathogen C. jejuni. We then focus our discussion on two C. jejuni Microbial Surface Components Recognizing Adhesive Matrix Molecule(s) (MSCRAMMs), termed CadF and FlpA, which have been demonstrated to contribute to C. jejuni colonization and pathogenesis. In vitro studies have determined that these two surface-exposed proteins bind to the extracellular matrix glycoprotein fibronectin (FN) in a specific manner. In vivo studies have shown that cadF and flpA deletion mutants exhibit impaired colonization of chickens compared to the wild-type strain. Additional studies have revealed that CadF and FlpA stimulate epithelial cell signaling pathways necessary for cell invasion. Interestingly, CadF and FlpA have distinct FN-binding domains, suggesting that the functions of these proteins are non-redundant. In summary, the binding of FN by C. jejuni CadF and FlpA adhesins has been demonstrated to contribute to adherence, invasion, and cell signaling.